Determinants of customer satisfaction in retail bankng at Dunkwa, Ghana - Appiah, Theresa Evelyn (2017)
A thesis submitted to the Department of Marketing and Corporate Strategy of the Kwame Nkrumah University of Science and Technology in partial fulfillment of the award of the degree of Master of Business Administration (Marketing).